Improving Control in the Digital Environment in the Field of Public Administration on the Example of the Republic of Mordovia - O. V. Shibileva; V. V. Parshutkina (Управленческие науки, 2023)
The purpose of the work is to study the features of the implementation of control activities in the digital environment and the directions of its improvement. The authors consider the need to implement the transition to “smart” state financial control (electronic SMART control [controlling]), based on a risk-oriented approach aimed at improving the quality of the effectiveness of control measures, reducing the burden on the controlled environment, identifying significant violations and risks. The article analyzes the most common software products designed to automate the processes of drawing up, analyzing and executing budgets at all levels, providing the opportunity to work in the mode of no communication with the financial authority, providing detailed information, which makes it possible to simplify control and increase its efficiency. The main stages of the development of control activities in the context of digital transformation are considered, indicating the implementation of some areas of improving the quality of control of the budget process and the effectiveness of public finance management in 2022, the formation of an integrated and coherent program for the introduction and implementation of electronic control, designed for the period up to 2027. The expediency of using the State Integrated Information System “Electronic Budget” (SIIS “EB”), which is a subsystem of information and analytical provision and support of users with the necessary information and means of analysis and reporting, designed to make reasonable and informed management decisions, is substantiated. On the example of the Republic of Mordovia: the practical experience of carrying out control and audit activities with the help of SIIS “EB”, the target of which is to increase the efficiency of financial and budgetary supervision, is considered; a plan for the implementation of control activities through the use of a single portal of the budgetary system, based on the compilation of electronic accounting documents and their subsequent transfer of the results to the audited object, is developed. The normative acts on internal and external state (municipal) financial control and financial audit are investigated. The following methods were used in the course of the work: synthesis, analysis, classification, detailing, comparison. The practical significance of the results lies in the theoretical justification of the need to improve control in the field of public administration, which provides the controllers (auditors) with the possibility of remote work with information about the functioning of facilities and obtaining detailed data. It is aimed at building and promoting more advanced preventive mechanisms in the field of public finance, contributing to the intensification of digital monitoring on the basis of a single electronic platform.